'Out Past / Self-Dramatization': Maurice Scully's Several Dances. Issue 1 (May 2016) - Huk, Romana
Abstract : What has lyric to do with any radical phenomenology's choreography? Maurice Scully in Several Dances asks that question, as he has for years now, alongside other poets of Ireland's avant-garde whose 'distinguishing (not inhibiting) feature', as Sarah Bennett writes (acknowledging the work of Alex Davis and Eric Falci before her) is that in it 'the lyric subject persists' – in tandem with, this essay argues, what she names 'an interest in perception … [which] is perhaps the most compelling commonality in these poets' work'. What distinguishes Scully's from the lyric phenomenology of American poets from William Carlos Williams (invoked throughout the volume) to George Oppen (also invoked) is that he queries existentialism's 'singular' approach to phenomena, achieved as Heidegger thought through the phenomenological 'bracketing' of individual (and communal) preconceptions from the perception of things. Cosmic – even theological – speculation enters in as Scully's poems move out past both self-centered lyric and twentieth-century cancellations of all preconceptions in the 'limit-thinking' and being-toward-death that phenomenology proposed for seeing past the self. Yet Scully works with mortality always in his sights too as he sings 'the Huuuman / Limit-at-tation Blues' (p.118) and, more vertiginously, considers both the undelimitability and the fragility of us.